-3.1+5.9+(-10)+3=

Simple and best practice solution for -3.1+5.9+(-10)+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.1+5.9+(-10)+3= equation:


Simplifying
-3.1 + 5.9 + (-10) + 3 = 0
-3.1 + 5.9 + -10 + 3 = 0

Combine like terms: -3.1 + 5.9 = 2.8
2.8 + -10 + 3 = 0

Combine like terms: 2.8 + -10 = -7.2
-7.2 + 3 = 0

Combine like terms: -7.2 + 3 = -4.2
-4.2 = 0

Solving
-4.2 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| sqrt(3m+4)=m | | 5a^2*1/6 | | 3(2x-1)+5=32 | | 5=1+2x | | 24x-7-16x+3=23x-8-15x+13 | | 4x-2(x-3)=x+12 | | 7(p+2)-4p=3p+14 | | 100y+300x*40=8400 | | 7/9*1/5*3/35 | | -1/6-6 | | -2/9*-1/4 | | [3+4x]=15 | | 100+300*40=8400 | | 21/1575 | | 2(v-3)-7=-3(-5v+1)-5u | | C/6=4 | | -4(-5w+6)-7w=5(w-5)-9 | | 2n+10=107.50 | | (-2/4)x+3=1 | | 142+2.7x=300 | | 7(n-2)-6=2n+8+n | | 900x=10 | | 2(x-.5)-6x= | | 142+2.7x=40 | | x+5-8=-2 | | -5(2w-6)+w=3(w+8) | | 3000x-6000(x+0.3)=93 | | 1=(-w+6) | | w(4-w^2)=8-w^2 | | [x-8]=11 | | 7(u+2)=42 | | 18x+4/17-17x=1/3 |

Equations solver categories